Vida nua e estado de exceção : a realidade das penitenciárias de Mato Grosso - Branco, Cintia Lopes (2017)
The restructuring of capital and the implementation of neoliberal policies has led to an increase in social exclusion, creating a need for more effective mechanisms to maintain social control and protect private property. With the advent of capitalism, prisons - conceived as places for the deprivation of liberty, where those who fail to adapt to the new economic and social order pay their debt to society in the form of time, the foundational measure of capital - arise as a solution, not as a way to produce docile bodies, but as a repository of social waste. Its denizens are stigmatized as a result of the neoliberal philosophies of individual success and meritocracy, both widely publicized by the media, which divides society into “good men” and “the enemies” based on pre-established criteria such as skin color, address, occupation, and the places they frequent. In addition to subjecting individuals to cruel and inhumane conditions, as well as the overcrowding caused by selective justice, the penitentiary system is ruled by exception. In these facilities, subhuman living conditions are accepted and even justified as necessary, since their denizens have taken on the role of homo sacer, people who may be killed or sacrificed to ensure the safety of others. The aim of the present study was to analyze the living conditions in the prisons of Mato Grosso, contrasting them with the human rights provisions of the Federal Constitution of 1988 and the Penal Code of 1984, in order to highlight the exceptional measures at work in the facilities investigated. This was achieved using a quantitative-qualitative approach, involving a questionnaire on the structure and services of each establishment administered to its wardens, as well as a review of documents and electronic sources, such as news articles published by state media over the years. The compilation and analysis of the data revealed that living conditions in the prisons of Mato Grosso do not comply with the requirements of the law, since suspects who are temporarily detained are not separated from those who have been convicted, and there are insufficient resources to allow for the individualization of punishment. Additionally, the vacuum of state regulation is filled by organized crime and drug trafficking, creating an independent and dangerous universe within the state apparatus. In many cases, religious institutions also exceed their legal bounds. The present study showed that the prison system in Mato Grosso is permeated by exceptional measures which contribute to the chaos and transform prisons into spaces where the law of the strongest prevails. This reality is masterfully manipulated by the media to promote the idea that some people no longer have any rights, as they have lost their judicial and social value, and have thus become disposable. The bare life to which inmates and other undesirables - black, brown, young, poor, women, indigenous peoples - are relegated transforms them into homo sacer, whose undignified lives are unworthy of living, and therefore liable to extermination.